Pulsating A-F Stars - Sánchez Arias, Julieta Paz (2019)
This Chapter provides a brief description of the different classes of pulsating A-F stars emphasising hybrids δ Sct-γ Dor stars. A modelling technique for hybrid δ Sct-γ Dor stars is presented along with the typical features that these stars “print” on their light curves and frequency spectra. Finally, we present a very different family of pulsating stars overlapping the region where pulsating A-F stars usually lie, the precursors of the so-called extremely low mass white dwarf stars. These stars have very similar atmospheric characteristics and their oscillation periods partially overlap making them difficult to discern. We discuss tools based on their seismic oscillation properties to distinguish them.